Ruminal degradability of supplements based on three native forages and adapted to the Colombian Amazonian piedmont - Riascos, A.; Reyes, J. J.; Valenciaga, D.; Apráez, J. E. (Cuban Journal of Agricultural Science, 2020)
In order to evaluate the in situ ruminal degradability of different supplements based on native forages and adapted to the Amazonian piedmont, three sheep with ruminal cannula were used. The evaluated treatments were: T1Control, T2 and T3 (0.5 kg concentrate + supplement with 20 and 40 % of Trichantera gigantea inclusion, respectively), T4 and T5 (0.5 kg concentrate + supplement with 20 and 40 % de Piptocoma discolor inclusion) and T6 and T7 (0.5 kg concentrate + supplement with 20 and 40 % Hibiscus rosa-sinensis inclusion). Analysis of variance according to completely random design with factorial arrangement (3x2) was carried out. The treatments with 20 % of H. rosa-sinensis inclusion reached an in situ ruminal degradability of DM and OM at 72 incubation hours higher than 84.65 and 72.79 %, respectively. The lower ruminal degradability of DM and OM at 72 incubation hours was for the treatment with T. gigantea at 40 %, followed by the treatment with P. discolors at 40 %. The treatments with H. rosa-sinensis at 20 % and T. gigantea at 20 % showed the highest effective degradation for DM and OM, respectively. The in situ degradability of DM, OM, NDF and ADF showed the highest values in the H. rosa-sinensis and P. discolor species, without differences between them, respect to T. gigantea. The inclusion of 20 % of forages in the supplement is a viable option from the nutritional supply point of view in supplementation programs. Key words: Piptocoma discolor, supplementation, Amazonia, Putumayo.